Constant Levels of Tau Phosphorylation in the Brain of htau Mice - Neddens, Joerg; Daurer, Magdalena; Loeffler, Tina; Alzola Aldamizetxebarria, Saioa; Flunkert, Stefanie; Hutter-Paier, Birgit (Frontiers in Molecular Neuroscience, 2020)
Excessive tau phosphorylation is the hallmark of tauopathies. Today’s research thus focusses on the development of drugs targeting this pathological feature. To test new drugs in preclinical studies, animal models are needed that properly mimic this pathological hallmark. The htau mouse is a well-known model expressing human but lacking murine tau, allowing to evaluate the efficacy of tau modifying compounds without interference from murine tau. Htau mice are well-characterized for tau pathology at older age, although it is often not specified on which genetic background analyzed animals were bred. Since it was shown that the genetic background can influence the pathology, we evaluated the phosphorylation status of young and adult htau mice on a C57BL/6J background by analyzing ptau Ser202 and ptau Ser396 levels in the cortex and hippocampus of 3 and 12 month old animals by immunofluorescent labelling. Additionally, we evaluated total tau, ptau Thr231 and ptau Thr181 in the soluble and insoluble brain fraction of 3-15 month old htau mice by immunosorbent assay. Our results show that ptau levels of all analyzed residues and age groups are similar without strong increases over age. These data show that tau is already phosphorylated at the age of 3 months suggesting that phosphorylation starts even earlier. The early start of tau phosphorylation in htau mice enables the use of these mice for efficacy studies already at very young age.